DIEAP flap for safe definitive autologous breast reconstruction. (April 2016) - Seidenstuecker, Katrin; van Waes, Carl; Munder, Beatrix I.; Claes, Karel E.Y.; Witzel, Christian; Roche, Nathalie; Stillaert, Filip; Mahajan, Ajay L.; Andree, Christoph; Blondeel, Phillip N.
Abstract: Background: Breast cancer is the commonest form of cancer in women affecting almost a quarter of a million patients in the US annually. 30 percent of these patients and patients with genetic mutations undergo removal of the breast, as highlighted in a high profile celebrity patient. Although breast reconstruction with free microvascular transfer of a DIEAP flap from the abdomen is an ideal form of reconstruction, there have been misgivings about the complexity and potential complications. This study was aimed at clearing these misunderstandings and establishing the value of this form of breast reconstruction. Methods: 1036 DIEAP flap breast reconstructions carried out at the University Hospital, Gent (five year period) and at the Sana Kliniken, Düsseldorf (three year period) were included prospectively. Comorbid factors like chemotherapy, radiotherapy, patient age >65 years, BMI >30 and smoking were recorded. Outcomes were evaluated over a mean follow up of 2 years. Results: Overall complication rate related to the reconstructed breast and donor abdominal area was 6.8 percent. Total flap loss was seen in only 0.8 percent. The mean operating time was less than five hours. Older age, higher BMI, chemotherapy and radiotherapy did not have a significant influence on complication rates, however smoking resulted in significant delay in wound healing in the breast (p = 0.025) and abdominal wounds (p = 0.019). Conclusion: The DIEAP flap is an excellent option for breast reconstruction, with a low level of donor site morbidity and complications. It is an autologous reconstruction that provides a stable long term result. Highlights: Large series with low complications reiterates its safety in breast reconstructions. These procedures can be safely carried out in a mean operating time of five hours. No significant complications with older age, high BMI, chemotherapy or radiotherapy. Smoking is not contraindicated in microvascular surgery, but affects wound healing.